Gaya Komunikasi Politik Persuasif Gubernur Dedi Mulyadi sebagai Pengambil Kebijakan Publik - Ivan, Ivan Issa Fathony (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2025)
This study aims to analyze the persuasive political communication style employed by Dedi Mulyadi in his efforts to build a positive public image and gain electoral support as a candidate for Governor of West Java. In the context of local politics, communication style serves as a strategic tool to foster emotional connections with the public, particularly through approaches that emphasize cultural values, simplicity, and social closeness. This research uses a descriptive qualitative method, with data collected through social media content observation and document analysis. The findings reveal that Dedi Mulyadi adopts a humanistic and narrative persuasive communication style, utilizing Sundanese cultural symbols, accessible language, and storytelling that evokes empathy. This strategy not only enhances his visibility and popularity but also strengthens public identification with him as a leader who preserves local traditions and remains close to ordinary people. His political communication reflects a successful integration of local content and a personal approach, proving effective in shaping public opinion and influencing voter preferences.